Bagaimana Remaja Menjadi Peer-Counselor di Masa Pandemi? - Permatasari, Nina; Makaria, Eklys Cheseda; Simon, Irene Maya; Setiawan, Muhammad Andri (citeus, 2021)
To optimally carry out their developmental tasks during the Covid-19 Pandemic, which affects psychosocial and mental health, teenagers require mentoring. One of those accompaniments may come from their peers. This study observes the way teenagers being peer-counselors during the Covid-19 pandemic. This quantitative research uses a descriptive survey design. Meanwhile, its populations were all participants of peer counseling training webinars conducted by the Centre of Guidance and Counselling Service of Lambung Mangkurat University. The 126 samples were selected using a random sampling technique live in South Borneo. The results convey that 32 percent, 78 percent, and 58 percent of teenagers actively being peer-counselors at the age of 16 years, at the high school age, and when the pandemic started, respectively. A 40 percent of teenagers explain that they choose to be peer counselors because they like to help their friends, 53 percent of them feel to have a superior personality that supports them to be peer counselors, while 27 percent of them contemplate on things they can suggest to help their friends as peer counselors. Additionally, 54 percent of teenagers wish to attain peer counselors' skills that can command the counselees' thoughts. Thus, teenagers have given relatively significant contributions as peer counselors during the Covid-19 pandemic.